2011
DOI: 10.1007/s10456-011-9244-y
|View full text |Cite
|
Sign up to set email alerts
|

Down-modulation of TNFSF15 in ovarian cancer by VEGF and MCP-1 is a pre-requisite for tumor neovascularization

Abstract: Persistent inflammation and neovascularization are critical to cancer development. In addition to upregulation of positive control mechanisms such as overexpression of angiogenic and inflammatory factors in the cancer microenvironment, loss of otherwise normally functioning negative control mechanisms is likely to be an important attribute. Insights into the down-modulation of such negative control mechanisms remain largely unclear, however. We show here that tumor necrosis factor superfamily-15 (TNFSF15), an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 54 publications
(66 reference statements)
6
67
0
Order By: Relevance
“…We also demonstrated that tumor cells are capable of stimulating such modified Th2 responses, featuring production of IL-10 and IL-4 and secretion of IgG4 by B cells. Also consistent with a tumor-associated inflammatory environment, VEGF, known to polarize Th2-biased cytokine production by PBMCs through induction of IL-10-secreting cells such as Tregs (53), along with well-described tumor-induced inflammatory mediators IL-6 and MCP-1 (53)(54)(55)(56), was found at significantly increased levels (P < 0.001; Supplemental Figure 3A Figure 8. n = 33.…”
Section: Discussionmentioning
confidence: 65%
“…We also demonstrated that tumor cells are capable of stimulating such modified Th2 responses, featuring production of IL-10 and IL-4 and secretion of IgG4 by B cells. Also consistent with a tumor-associated inflammatory environment, VEGF, known to polarize Th2-biased cytokine production by PBMCs through induction of IL-10-secreting cells such as Tregs (53), along with well-described tumor-induced inflammatory mediators IL-6 and MCP-1 (53)(54)(55)(56), was found at significantly increased levels (P < 0.001; Supplemental Figure 3A Figure 8. n = 33.…”
Section: Discussionmentioning
confidence: 65%
“…We showed previously that TNFSF15 gene expression in EC is down-regulated by VEGF produced by ovarian cancer cells (42). This indicates that the actions of a positive modulator of angiogenesis, namely VEGF, may lead to the removal from tumor microenvironment of a negative modulator of angiogenesis, namely TNFSF15, which would otherwise functions as an obstacle in the initiation or continuation of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…It also inhibits Lin − -Sca-1 + EPC differentiation into EC (6) and EPC incorporation into tumor vasculature in murine models (10). TNFSF15 expression is absent or marginal in tumor vasculatures in various cancers (40)(41)(42), increased in irritable bowel syndrome (43), and down-regulated in wound tissues (44). TNFSF15 down-regulation in ovarian cancer is facilitated by VEGF secreted by cancer cells as well as by other inflammatory cytokines (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, treatment with a peptide that interferes with G-protein coupled receptors, X1/2pal-i3 pepducin, hindered PAR1 activation by MMP1 (74). Recent findings suggest that specific modulators that impede angiogenesis, such as tumor necrosis factor superfamily-15 (TNFSF15), are downregulated by VEGF and CCL2, which are not only released by cancer cells, and therefore, emphasize the importance of contributing cell populations to neoangiogenesis (75).…”
Section: Angiogenic Vasculature Is Required For Tumor Growthmentioning
confidence: 99%